Forensic Odontology and Its Medico-Legal Applications - Sriram Kaliamoorthy; Vijayparthiban Sethuraman; Lakshmanan Vijayalakshmi; Sakthivel Sambasivam (Indian Journal of Forensic Medicine & Toxicology, 2021)
Forensic Odontology is a specialty field of dentistry that analyses dental evidence for the department of justice. Forensic dentistry encompasses all dental specialties and the isolation of this industry from other dental fields is nearly difficult. The objective of the paper is to discuss and describe the applications of forensic odontology in the fields of justice and crime solving.